Experiences of psychosocial coping at international matches in professional volleyball players of the Peruvian national team - Cuba-Martínez, Cristina (2023)
The present study seeks to know how psychosocial coping are experienced at international matches in professional volleyball players of the Peruvian national team. A qualitative methodology with phenomenological-hermeneutic design was used. Twelve semi-structured interviews were conducted with professional volleyball players belonging to the Peruvian women's team in the senior category. From the analysis, three categories, nine subcategories and seven codes were identified, which comprise the 189 units of analysis. The results showed that the main coping strategies used by the athletes are personal logical analysis and the analysis of the opposing team, the use of effort, the search for professional support and mental imagery. It is concluded that professional volleyball players in Peru mainly use task-oriented coping, carried out activities that allow them to feel capable and play an essential role in decision-making during competitions.